1994
DOI: 10.1111/j.1365-2621.1994.tb08115.x
|View full text |Cite
|
Sign up to set email alerts
|

Myofibrillar Protein Gelation: Viscoelastic Changes Related to Heating Procedures

Abstract: Dynamic rheological properties were investigated during gelation of chicken myofibrillar protein as influenced by heating procedures, Thermal scan (l"C/min) of myofibril suspensions in 0.6M NaCl @H 6.0) induced a major transition in storage modulus (G', peak 48°C) preceded by a transition in protein-protein aggregation (46°C) and accompanied by a marked reduction in actomyosin solubility. Preheating at 50°C diminished the transition and resulted in increased final G' value. Isothermal heating produced complex,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
38
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(51 citation statements)
references
References 17 publications
13
38
0
Order By: Relevance
“…CyTA -Journal of Food 65 Xiong and Blanchard (1994) found that the myofibrillar protein storage modulus value changed at 46°C during heating, and Samejima, Ishioroshi, and Yasui (1981) found that rabbit myosin had two elastic transition points; one at 43°C and another at 53°C, which is similar to the findings of the present research. The storage modulus and loss modulus values of gel were stable when the temperature rose to about 70°C, which is consistent with the results of myofibrillar proteins (Westphalen, Briggs, & Lonergan, 2006).…”
Section: Rheological Propertiessupporting
confidence: 92%
“…CyTA -Journal of Food 65 Xiong and Blanchard (1994) found that the myofibrillar protein storage modulus value changed at 46°C during heating, and Samejima, Ishioroshi, and Yasui (1981) found that rabbit myosin had two elastic transition points; one at 43°C and another at 53°C, which is similar to the findings of the present research. The storage modulus and loss modulus values of gel were stable when the temperature rose to about 70°C, which is consistent with the results of myofibrillar proteins (Westphalen, Briggs, & Lonergan, 2006).…”
Section: Rheological Propertiessupporting
confidence: 92%
“…Such a profile has been reported with minced meat from rainbow trout (Autio et al, 1989) and carp actomyosin paste (Sano et al, 1989), and also with myofibrillar protein solution from rabbit (Culioli et al, 1993;Boyer et al, 1996a), poultry (Xiong and Blanchard, 1994) and beef myosin (Fretheim et al, 1986).…”
Section: White Muscle Rheological Measurementsmentioning
confidence: 69%
“…Compared with rabbit (Boyer et al, 1996a) and poultry (Xiong and Blanchard, 1994), using similar measurement conditions, brown trout seemed to have low gelling ability.…”
Section: White Muscle Rheological Measurementsmentioning
confidence: 87%
“…Literature analysis of the values of molecular weight and electrophoretic separation of proteins from muscle tissues made it possible to find a series of different proteins in the myofibril preparation [26,28,30,32]. Probably above the myosin heavy chain band (205 kDa), cytoskeletal proteins such as e.g.…”
Section: Electrophoretic Analysismentioning
confidence: 99%